‘Master switch’ genes for disease resistance in rice: lessons learnt and lessons to learn - Singh, Pooja; Bawankar, Raksha; Gothandam, K.M.; Subashkumar, Rathinasamy; Vivekanandhan, Govindasamy; Thayumanvan, Tha.; Babu, Subramanian (Research in Biotechnology, 2012)
Evolving disease resistance rice variety has become a continuous encounter from plant pathologists’ point of view, against the changing scenario in the severity of various fungal, bacterial and viral diseases. Although we are successful to some extent in developing some varieties through conventional and molecular breeding, the recent genome level data indicate that we have only disclosed the tip of an iceberg. The strategy of introducing single foreign gene for every disease crop plants like rice, suffers not only from regulatory issues of genetically modified rice but also lack of sustainability under field tests. This is attributed to the fact that pathogen resistance is mediated by complex networking of genes and their protein products. Transcription factors that control expression of hundreds of other genes offer themselves as valid candidate for key gene transgenics. Rice transcription factors like Osmyb4 is observed to regulate many PR protein genes and genes involved in post infection defense. Hence, over-expressing these gene(s) in cultivated variety(s) would result in transgenic rice resistant to multiple diseases. The level of constitutive expression of these genes should however be evaluated in major cultivated varieties of rice and a correlation of their native level of resistance/susceptibility to diseases may complement the approach.